Intelligent Iraqi Health System (IIHS) using Online Analytical Process (OLAP) model - Khraibet, Hayder Naser; Mousa, Ayad Hameed; Abu Bakar, Muhamad Shahbani (2013)
Intelligent Iraqi Health System (IIHS) is an intelligence system using a set of methodologies, architectures, processes, and business intelligence technology.These technologies integrate huge amounts of right data and present the information in the given time.IIHS analyzes the data from operational systems into meaningful and useful information by using data warehousing technologies.The main function of IIHS technology is to produce analytical report, which helps the management make right decision making. Business Intelligence (BI) component, called Data Warehouse (DW) is a database designed to support decision making. The DW takes data from operational applications and loads the data to the destination DW to provide the information for supporting decision making.The Iraqi Ministry of Health, which is responsible agency to manage health activities in Iraq, needs an analytical report for strategic decision making.This paper has explained how to design and develop (IIHS) by using Online Analytical Process (OLAP) model to be used by decision makers in the Iraqi Ministry of Health.Computer System Usability Questionnaire (CSUQ) was used to evaluate the prototype of the IIHS.Finally, this paper provides a guide for BI developers and decision maker in the Iraqi Ministry of Health the benefit of OLAP model for developing information systems.